PERSPEKTIF POLITIK HIJAU DALAM UPAYA MENANGANI ANCAMAN SAMPAH IMPOR DI KOTA BATAM - Justine, Nico Andreas; Pramana, Gede Indra; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2023)
This research aims to describe the Batam City Government's policy in dealing with the threat of imported waste. This problem is interesting to study because Batam City is one of the areas that is quite vulnerable to illegal waste smuggling. This research uses green political theory as an analytical framework in reading the policies formed by the Batam City Government to overcome this threat. The method used is a qualitative-explanatory method using primary and secondary data. The results of this research indicate that the Batam City Government cannot make effective policies in dealing with the threat of imported waste. This can happen because of the lack of authority of local governments in dealing with environmental management matters. Regional governments cannot act beyond the actions of the central government, so regional governments only follow instructions. This resulted in the Batam City Government being slow to respond to this problem. Apart from that, the waste management infrastructure in Batam City is not yet running optimally.